Social participation of women with breast cancer - Nikolic, Snežana Janko; Ilič-Stošović, Danijela; Kolarević, Ivan; Djurdjević, Ana; Ilić, Snežana; Djuričić, Milica (Vojnosanitetski pregled, 2015)
Background/Aim. The general problems of persons with malignant diseases (stages of asthenia, chronic fatigue and exhaustion, followed by depression and anxiety) lead to a decrease in functional abilities and a declining quality of life. The aim of this study was to determine the level of difficulty, the type of required assistance and the level of satisfaction that derives from maintaining life habits. The study also examined the correlation between the level of accomplishment of life habits and the level of satisfaction with how they are maintained. Methods. The research was conducted at the Military Medical Academy in Belgrade and in the “Get Together” Association of Women with Breast Cancer from June to September 2012 on a sample of 30 women. A standardised questionnaire, Assessment of Life Habits – LIFE-H v.3.0, was administered. Results. The lowest level of maintaining normal activities was related to education, housing and recreation. The greatest need for support to maintain normal activities was in the domains of housing, interpersonal relationships and employment. The greatest satisfaction in the accomplishment of normal activities was observed in the domains of mobility, nutrition and housing, and the lowest level of satisfaction was in the domains of recreation, communication and interpersonal relationships. The correlation between the level of accomplishment of normal activities and the level of satisfaction was the highest in the domains of general physical activity, responsibility and life in a community; the lowest level was in the domains of personal hygiene, housing, mobility, employment and recreation (p < 0.001). Conclusion. The results indicate that research participants found it more difficult to maintain their social activities than their everyday activities. This clearly indicates the necessity to develop and implement special advisory and educational programs aimed at preventing social exclusion and to strengthen and support personal resources in the area of the social roles of women with breast cancer.